Balance factors affecting the quality of life in patients with knee osteoarthritis - Tian-Shyug Lee; Hsiang-Chuan Liu; Shih-Pin Lee; Yi-Wei Kao (AOSIS, 2022)
Background: Knee osteoarthritis (OA) affects the quality of life (QOL) and balance control of elderly people; our study explored the balance factors that affected the QOL in patients with knee OA. Objectives: To determine the balance factors that affected the QOL of patients with knee OA who attended general clinics. Method: A total of 30 healthy controls and 60 patients with mild-to-moderate bilateral knee OA, all aged 55-75 years, were enrolled in our cross-sectional study. All participants were interviewed; the Medical Outcomes Study 36-Item Short-Form Health Survey was used to assess their QOL in eight dimensions, and the Balance Master System was used to evaluate their balance control according to six parameters. Descriptive statistics were used to reduce the data; an independent t-test determined differences between the two groups, and a multiple regression analysis was undertaken to establish associations between variables from the balance control test and SH36 physical and mental health components. The level of statistical significance was set at 5%. Results: In the OA group, significant negative correlations were observed between sway velocity and the physical health component (p = 0.003) and between sway velocity and the mental health component (p = 0.006). Thus, sway velocity had a major impact on the QOL of patients with knee OA. Conclusions: The sway velocity at the centre of gravity in balance control was a crucial factor for determining the QOL of patients with bilateral knee OA. Clinical implications: Sway velocity is a key factor affecting the QOL and may provide a basis to formulate preventive actions and design treatment goals for patients with knee OA.